THE KNOWLEDGE OF NURSING STUDENTS ON ALCOHOL AND DRUGS - Sandra Cristina Pillon; Margarita A. Villar Luis (Universidade Federal de Goias, 2003)
This study aimed to know the knowledge acquired by undergraduate nursing students concerningalcohol and drugs. The research was developed in 1998 at the University of São Paulo at Ribeirão Preto College ofNursing. Results: most students did not remember or attend classes discussing that topic; they had never dealtwith substance users; however, they correctly responded to the concepts of substance addiction, tolerance andabstinence; they expressed their opinion that the topic must be included in the nursing curriculum. Conclusion: theknowledge acquired by students is deficient with regard tocontent or to the way it is addressed once the datasuggested that content was not adequately incorporated, although students were interested in the topic.